Business Education For Sustainable Development: The Case of Romanian Universities - Răzvan V. Mustaţă; Carmen Giorgiana Bonaci; Cristina Hintea; Bogdana Neamţu (Amfiteatru Economic)
Our study approaches the concept of sustainable development from a business perspective by looking into how universities can contribute to incorporating sustainability in the formation of future business professionals. The main objective of our paper is to develop an analysis that offers a current overview on the business higher education system as a source of education for sustainable development, particularly in the Romanian context. The employed research methodology mainly relies on content analysis of selected universities’ curricula and syllabuses as available on their websites. The obtained results document the current state of facts and allow suggestions for future improvements. Overall, our findings bring support to previous studies in suggesting that Romanian higher education should adjust more to the realities of the current business environment. Our study contributes to the literature on sustainable development by providing insights into the Romanian business higher education particularities, which might prove helpful for academics and students, as well as practitioners.